The Organic Law 4/2000: technical and legal analysis of its major developments - Charro Baena, Pilar; Ruiz de Huidobro de Carlos, José María (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
This articles offers a technical-legal analysis of the Organic Law 4/2000, which determines the new legal situation of foreigners and immigration in Spain. It tries to suggest a first legal interpretation of the recently approved law, determining its meaning in view of its effectiveness and application. Although it offers a global approach to the normative meaning and the contents of the Organic Law, for reasons of opportunity, only those matters which are original or that directly concern the reformist aim of the Organic Law, that is, to make immigrants’ integration into society easier, have been selected for close analysis. The conclusion of the exposition is the poor technical quality of the legal text, which will make more difficult its interpretation and application, diminishing its aim to achieve integration.